Three Cases of Severe Invasive Infections Caused by Campylobacter rectus and First Report of Fatal C. rectus Infection - Lam, Jimmy Y. W. (American Society for Microbiology, 2011)
We report the first fatal case of Campylobacter rectus infection due to a subdural empyema and ruptured mycotic intracranial aneurysm and two cases of limb-threatening C. rectus necrotizing soft tissue and bone infection and empyema thoracis that responded to amoxicillin-clavulanate and surgical debridement and drainage. All three strains were identified by 16S rRNA sequencing.